Species Composition, Utilization and Conservation Status of Plant Species in Gmelina arborea Agroforestry System in Boalemo Regency - Kadir, Zen Setiawan; Baderan, Dewi Wahyuni K.; Hamidun, Marini Susanti; Utina, Ramli; Dunggio, Iswan (Indonesian Journal of Chemistry and Environment, 2024)
Agroforestry is a land-use system that integrates trees, crops, and livestock to improve sustainability and resilience in agricultural practices. This research aimed to determine the composition of plant species in the White Teak Agroforestry, the utilization of plants and the conservation status of plant species in the White Teak agroforestry system. Quantitative approach was applied with plant data collection carried out by tracing the research location and observing all existing plant species accompanied by taking pictures using a digital camera. The results of the study indicate that the agroforestry system has significant potential in supporting environmental sustainability and community welfare. The results revealed there were 33 plant species found in the agroforestry, 23 of them were plants that distributed across various regions in Indonesia and 14 are classified as Least Concern by the IUCN Red List.